Deoxygenative photochemical alkylation of secondary amides enables a streamlined synthesis of substituted amines - Antonio Pulcinella; Stefano Bonciolini; Robin Stuhr; Damiano Diprima; Minh Thao Tran; Magnus Johansson; Axel Jacobi von Wangelin; Timothy Noël (Nature Communications)
Abstract Secondary amines are vital functional groups in pharmaceuticals, agrochemicals, and natural products, necessitating efficient synthetic methods. Traditional approaches, including N-monoalkylation and reductive amination, suffer from limitations such as poor chemoselectivity and complexity. Herein, we present a streamlined deoxygenative photochemical alkylation of secondary amides, enabling the efficient synthesis of α-branched secondary amines. Our method leverages triflic anhydride-mediated semi-reduction of amides to imines, followed by a photochemical radical alkylation step. This approach broadens the synthetic utility of amides, facilitating late-stage modifications of drug-like molecules and the synthesis of saturated N-substituted heterocycles. The pivotal role of flow technology in developing a scalable and robust process underscores the practicality of this method, significantly expanding the organic chemist’s toolbox for complex amine synthesis.